Florestas urbanas: método de avaliação para gestão das áreas verdes - Mazzarotto, Angelo Augusto Valles de Sá (2008)
The diagnosis the quality of the Urban Forests precedes a good planning. Methods that show a good prospect, not only favor comparisons, as they provide more solid techniques bases, necessary for the sustainability. This method main objective is to evaluate by interaction and balance of a group of indices, that consider qualiquantitative aspects of the Urban Forests, evaluating elements, as: arborization in streets, squares and forests. For this proposal several indices were selected in a literature revision, being them selected following criterias that represent the contribution of the Urban Forests to the society, as in the aesthetic aspects, quality of air, flood control and temperatures. The indices had been certified in its trustworthiness, representation and then grouped in two sets, macro and mícron ambient. The first group composed to evaluate ampler characteristics, inherent to a set of individuals and the second by characteristics of the vegetal individual itself, as aspect of the root. To the indices weights had been attributed, differentiating them by its representations inside of the method. As result, a tool is considered that uses the Barometer of the sustainability for the intersection of the two axles, ambient macro and micron, providing only one reading of the sustainability condition. Tested in two areas, the campus of the Positivo University and the Botanical Garden, both located in the city of Curitiba, Paraná, has shown to be albe to diagnose the condition of susteainability of the areas.